Probable Creatures - a Commentary - Brenna, Brita (Tidsskrift for kulturforskning, 2008)
In Brian Ogilvie’s essay we encounter insects depicted as flying, hopping or crawling across disciplinary boundaries in early modern Europe. Before entomology was named and transformed into a discipline around the middle of the 18th century, those observing and describing insects were operating within what could be defined as different communities of practice (cf. Star and Bowker 1999). These would sustain separate conventions, aims and codes of representation, but at the same time the small creatures were straddling the borders separating them, these borders being both tightly drawn and highly permeable, as we can read in Ogilvie’s article. They were tightly drawn as the practitioners identified themselves as involved in different projects, and they were on the other hand highly permeable as the insects and their representations travelled easily from one community to the other.